Assessment of dentists’ knowledge in utilization of adhesives in complete dentures - Sales, Inaê Ferreira; Carneiro, Camila Alves; Porto, Vinicius Carvalho (Brazilian Dental Science, 2025)
Objective: To assess dentists’ knowledge regarding adhesive usage in complete dentures (CD). Material and Methods: Data collection was conducted through a questionnaire administered via the Google Forms platform. The study included dentists with active Regional Dentistry Council (CDR) registration, both general practitioners and prosthodontics specialists, practicing within Brazilian territory. Results: The findings revealed that, although adhesives positively impact denture stability, retention, masticatory performance, comfort, and patient satisfaction, there is still limited knowledge among professionals regarding their proper use. Conclusion: Results highlighted the professionals’ lack of knowledge on the subject and the consequent importance of continuous professional development to ensure high-quality dental care.KEYWORDSComplete denture; Denture adhesives; Fixatives; Knowlegde; Practice.